Canis lupus familiaris and diclofenac: understanding the potential risks of this association - Lohmann-Menezes, Bruna; Giarolla, Jeanine; da Silva-Santos, Yasmin; Petri, Giuliana; Epiphanio, Sabrina (Frontiers in Veterinary Science, 2024)
In many homes worldwide, dogs are considered part of the family. Every possible care is given to animals, including drug treatments. However, many animal guardians, in an attempt to minimize pain or improve the quality of life of their dogs, provide drugs without a veterinarian’s prescription. Diclofenac, a non-steroidal anti-inflammatory drug that acts on cyclooxygenase-1 and cyclooxygenase-2 enzymes, is associated with several adverse events, especially related to the gastrointestinal tract, both in humans and pet animals. Therefore, the availability of information about the effects of this drug in different species is always essential. This narrative review aims to present adverse reactions the domestic dog (Canis lupus familiaris) can suffer when exposed to diclofenac. Scientific publications, books, and case reports were consulted, and inquiries were also carried out with regulatory agencies. Many reports of suspected adverse reactions, especially related to the gastrointestinal tract, were found. Other clinical manifestations and lesions were also identified in the cardiovascular system, liver, kidneys, and hematological examinations. Therefore, diclofenac may constitute a hazard to dogs, mainly due to possible damage to the gastrointestinal tract. This fact reinforces the need to seek veterinary advice before providing any drug to animals, in addition to recommendations on ensuring the correct storage of medications to avoid accidental exposure.